The Effect Of Iron Supplement Consumption On HB Levels In Pregnant Women At The Bangko Jaya Community Health Center, Rokan Hilir Regency - Rafika Rafika; Nia Desriva; Fatma Nadia; Wira Ekdeni Aifa (International Journal of Health Engineering and Technology, 2026)
Iron deficiency anemia in pregnant women is a serious health problem in Indonesia with a prevalence of 27.7%, mainly due to low compliance with iron supplement consumption despite the implementation of the Iron Supplement Tablet (TTD) program. This study aims to analyze the relationship between compliance with iron supplement consumption and hemoglobin (Hb) levels in pregnant women at the Bangko Jaya Community Health Center, Rokan Hilir Regency. Using a quantitative descriptive cross-sectional design, a population of 85 pregnant women in the second and third trimesters was taken by total sampling. Instruments in the form of a compliance questionnaire and Hb data from medical records were analyzed univariately (frequency) and bivariately (Chi-Square). The results showed that 69.4% of respondents were compliant with supplement consumption, 68.2% were not anemic, with a significant relationship (p=0.00; OR=0.17, 95% CI: 0.02-1.18). It was concluded that compliance with iron supplement consumption was significantly associated with Hb levels in pregnant women, recommending strengthening ANC counseling.